Geomorphic changes of a landslide dam by overtopping erosion - Yoschino, K.; Uchida, T.; Schimizu, T.; Tamura, K. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value=""1":2,"2":"Clarifying geomorphic changes to landslide dams following overtopping is important for mitigation of future disasters. Past modelling experiments have not provided adequate information about geomorphic and grain size distribution changes at landslide dams. We used field survey data, aerial photographs, and LiDAR imagery to analyze the geomorphic changes of a landslide dam formed during the 2008 Iwate and Miyagi inland earthquake and the effect of subsequent overtopping erosion on the dam morphology and grain size distribution of the sediments. Our field survey data showed clear evidence of armour coating in the stream bed. We used LiDAR data sets recorded before overtopping, shortly after overtopping, and around 120 and 140 days after overtopping to clarify geomorphic changes. Our LiDAR data analysis revealed that around 30% of sediment eroded by overtopping was deposited within about 200 m of the lower end of the landslide dam, and that after overtopping, erosion and deposition gradually returned the riverbed gradient to close to that which existed before the landslide. Moreover, we showed that near the flat head of the landslide dam, the erosional channel was narrow and deep. Farther downstream from the flat head, the erosional channel was shallower and wider."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">Clarifying geomorphic changes to landslide dams following overtopping is important for mitigation of future disasters. Past modelling experiments have not provided adequate information about geomorphic and grain size distribution changes at landslide dams. We used field survey data, aerial photographs, and LiDAR imagery to analyze the geomorphic changes of a landslide dam formed during the 2008 Iwate and Miyagi inland earthquake and the effect of subsequent overtopping erosion on the dam morphology and grain size distribution of the sediments. Our field survey data showed clear evidence of armour coating in the stream bed. We used LiDAR data sets recorded before overtopping, shortly after overtopping, and around 120 and 140 days after overtopping to clarify geomorphic changes. Our LiDAR data analysis revealed that around 30% of sediment eroded by overtopping was deposited within about 200 m of the lower end of the landslide dam, and that after overtopping, erosion and deposition gradually returned the riverbed gradient to close to that which existed before the landslide. Moreover, we showed that near the flat head of the landslide dam, the erosional channel was narrow and deep. Farther downstream from the flat head, the erosional channel was shallower and wider.